2022
DOI: 10.1021/acs.inorgchem.2c00150
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(III) Complexes for Light-Activated Delivery of Acetylacetonate-BODIPY, Cellular Imaging, and Photodynamic Therapy

Abstract: Cobalt­(III) complexes [Co­(TPA)­(L1)]­(ClO4)2 (1), [Co­(4-COOH-TPA)­(L1)]­(ClO4)2 (2), [Co­(TPA)­(L2)]­Cl2 (3), and [Co­(4-COOH-TPA)­(L2)]­Cl2 (4) having acetylacetonate-linked boron-dipyrromethene ligands (L 1 , acac-BODIPY; L 2 , acac-diiodo-BODIPY) were prepared and characterized, and their utility as bioimaging and phototherapeutic agents was evaluated (TPA, tris-(2-pyridylmethyl)­amine; 4-COOH-TPA, 2-((bis-(2-pyridylmethyl)­amino)­methyl)­isonicotinic acid). HL 1 , HL 2 , and complex 1 were structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 70 publications
(110 reference statements)
0
22
0
Order By: Relevance
“…However, it is challenging to develop luminescent complexes with first-row transition metals due to the efficient nonradiative deactivation via the low-lying MC excited states . Thus, these complexes typically require a fluorescent ligand for tracking their intracellular localization. Nevertheless, recent findings have demonstrated that with a rationally designed ligand framework, these complexes can be made luminescent with long excited-state lifetimes in solution at room temperature; , representative examples include those of vanadium, chromium, manganese, iron, cobalt, , nickel, and copper. Luminescent complexes of other earth-abundant metals such as zirconium, molybdenum, and tungsten have also been developed for applications in OLEDs and photocatalysis. Conversely, the efficient nonradiative decays of first-row transition metal complexes can be harnessed to develop PTAs for photoacoustic imaging and PTT when the complexes display intense NIR absorption. Thus, it is foreseeable that a strategic design of ligand systems will lead to the development of photoactive earth-abundant transition metal complexes for biosensing, bioimaging, and phototherapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is challenging to develop luminescent complexes with first-row transition metals due to the efficient nonradiative deactivation via the low-lying MC excited states . Thus, these complexes typically require a fluorescent ligand for tracking their intracellular localization. Nevertheless, recent findings have demonstrated that with a rationally designed ligand framework, these complexes can be made luminescent with long excited-state lifetimes in solution at room temperature; , representative examples include those of vanadium, chromium, manganese, iron, cobalt, , nickel, and copper. Luminescent complexes of other earth-abundant metals such as zirconium, molybdenum, and tungsten have also been developed for applications in OLEDs and photocatalysis. Conversely, the efficient nonradiative decays of first-row transition metal complexes can be harnessed to develop PTAs for photoacoustic imaging and PTT when the complexes display intense NIR absorption. Thus, it is foreseeable that a strategic design of ligand systems will lead to the development of photoactive earth-abundant transition metal complexes for biosensing, bioimaging, and phototherapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many Co III complexes have been reported to show visible light‐catalyzed toxicity to cancer cells through oxidative stress generation [19,22b,37] . The intense visible light band of 3 and 4 at around 425 nm indicated that these complexes may induce cancer cell death on white light excitation.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] In general metal-based photo-sensitizers contain photoresponsive ligand(s) that lead to light absorption properties in the visible region. [7][8][9][10][11][12][13][14][15][18][19][20] Over the past few years, curcumin, a bright yellow polyphenolic constituent of turmeric, has been used as an efficient photoresponsive ligand to design metal-based photosensitizers. [21][22][23][24][25][26][27] Besides its photosensitizing capabilities under visible light, it promotes apoptosis in cancerous cells by changing NF-kB functioning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations